Polemical Aspects of Concept and Essence of Procedural Time Limits within Administrative Procedure - Розум, Ігор Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
In this scientific paper, the author analyses core polemical theoretical aspects of scientific perception and understanding of the essence and legal nature of procedural time limits within the administrative procedure in an integrated manner. Special attention is paid to the fact that a lawmaker has formulated the concept of procedural time limits in Part 1, Article 101 of the Code of Administrative Legal Proceedings of Ukraine using absolutely tautological categories (the mentioned definition clearly stipulates that procedural time limits are time limits determined by law or court...). Finally, the mentioned above does not allow covering the phenomenon of their legal nature and context in full. From the perspective of the interconnection between the category of time and the category of material, such elements of time as a moment and duration, as well as the connection between the fact of time commencement/end and context-specific legal consequences, the author provides his own definition of the category of ‘procedural time limits within the administrative procedure.’ Based on the mentioned definition, the system of characteristics of such time limits is determined: these time limits are time limits determined by law or administrative court; their commencement and end trigger clear legal consequences (including procedural consequences); parties to the administrative procedure take procedural actions within these time limits. In addition, this scientific paper determines the peculiarities of the correlation between the time limits for having recourse to the administrative court and procedural time limits within the administrative procedure. The raised issue states that nowadays, there are two context-opposing scientific approaches, which stipulate that, first, time limits for having recourse to the administrative court should be recognised as substantive as they are directly related to the exercise of the rights and freedoms of an authorised person, and, second, such time limits should be referred to procedural time limits within the administrative procedure. Following the comprehensive analysis of the legal nature, essence, characteristics and standard regulation of the time limits for having recourse to the administrative court, it is reasonable to conclude that such time limits are one of types of the procedural time limits within the administrative procedure. In this context, it should be also noted that distinguishing time limits for having recourse to the administrative court in Articles 99 and 100, Chapter VIII, the Code of Administrative Legal Proceedings of Ukraine, is related to the fact that these procedural legal provisions simultaneously stipulate for their duration and calculation method, rather than to the fact that a lawmaker refers them to a separate group of time limits within the administrative procedure and they coexist with procedural time limits.